Bio-fabricated silver nanoparticles: therapeutic evaluation as a potential nanodrug against cervical and liver cancer cells - Irshad Ahamad; Masood Nadeem; M. Moshahid Alam Rizvi; Tasneem Fatma (Discover Nano)
Abstract Nanobiotechnology has grown rapidly and is now widely used in the diagnosis and treatment of modern diseases. Biosynthesized silver nanoparticles (AgNPs) are eco-friendly, cost-effective, biocompatible route, and have biomedical properties at minimal concentrations. In the present study extract of cyanobacterium (Anabaena variabilis) was utilized to synthesize facile, reliable AgNPs, further biosynthesized AgNPs were characterized by physicochemical techniques. The atomic force microscope study confirmed the shape of AgNPs while the scanning electron microscopy study revealed 17 to 35 nm in the size range. The zeta potential value of -19.5 mV demonstrated the repulsion effect between the particles, which prevents their aggregations while the heating stability of AgNPs was confirmed by Thermogravimetry differential thermal analysis. Another important characteristic, such as elemental constituent of AgNPs was determined by inductively coupled plasma mass spectrometry and was observed 94.24, 95.19, 97.06, and 99.34% of silver present in their respective concentrations of AgNPs. In vitro cytotoxicity of AgNPs was screened on HeLa, SiHa, (Cervical carcinoma), and HepG2 (Human hepatocellular carcinoma), cell lines. To evaluate the biocompatibility of AgNPs immortalized human embryonic kidney (HEK-293) cell line was used. The IC50 values of AgNPs are were observed as 23.76 ± 2.4 µg/mL, 11.21 ± 1.7 µg/mL, and 22.27 ± 1.8 µg/mL against HeLa, SiHa and HepG2 cell lines respectively. AgNPs demonstrated the biocompatible nature against HEK-293 cells, Normal cell line (HEK-293) cytotoxicity results showed exhibited ≥ 95% cell viability at all the concentrations. During the DAPI (4’,6-diamidino-2-phenylindole) staining study IC50 dose of AgNPs on cancer cell lines (HeLa, SiHa, and HepG2) showed nuclear morphological alterations which indicate the DNA damage and apoptosis in cancer cells. AgNPs treated cancer cells increased the cells number in the S phase while decreased the number of cells in the G0-G1 and G2/M phases of the cell cycle in all three cancer cells compared to the control. Graphical Abstract